Comparative Study of Outcome of Bothbone Forearm Fracture Treated with Rigid Fixation Vs Hybrid Fixation - Vittal Varma, Manthena Ramakrishna; Sharma, Abhishek; Weling, Ameya; Shah, Aditya (Journal of Neonatal Surgery, 2025)
Forearm fractures involving both the radius and ulna diaphysis are complex orthopaedic injuries requiring precise anatomical restoration for functional recovery. Traditional treatment involves rigid fixation using plates for both bones. However, hybrid fixation, combining intramedullary nailing (IMN) of the ulna with plate fixation of the radius, has emerged as a less invasive alternative. Aim The Aim Of The Study Is To Compare Outcome Of Bothbone Forearm Fracture Treated With Rigid Fixation Vs Hybrid Fixation. Objective To observe and compare differences in clinical outcomes of different fixation methods for both-bone diaphyseal fractures plate fixation to radius and ulna and intramedullary nailing of ulna and plate fixation of radius To assess the time related to mobilize patients post operatively in both the methods To assess union and evaluate union time for both methods intramedullary nailing of ulna and plate fixation of radius To observe complications in the study of both fixation types. To compare Anderson score for both bone diaphyseal fractures plate fixation to radius and ulna and intramedullary nailing of ulna and plate fixation of radius Methodology A prospective, comparative study was conducted at Krishna Hospital, Karad, over 18 months involving 48 patients with diaphyseal fractures of both forearm bones. Patients were randomized into two groups: Group 1 received rigid fixation (plating of both bones), and Group 2 received hybrid fixation (IMN for ulna + plate for radius). Functional outcomes, union rates, operative times, and complications were evaluated using standard statistical tools. Results Hybrid fixation demonstrated significantly shorter mean union time (8.9 weeks vs 10.4 weeks, p=0.03), superior flexion/extension and pronation/supination ranges, and lower rates of malunion (4.2% vs 12.5%, p=0.03). Functional outcomes based on Anderson scores favoured hybrid fixation, especially in distal fractures. Both groups had comparable mobilization times and similar infection rates. Discussion Hybrid fixation offers the benefits of minimally invasive surgery while maintaining sufficient biomechanical stability. It yielded better functional outcomes, faster union, and fewer complications in select fracture types. Conclusion Hybrid fixation is a viable alternative to rigid fixation for adult both-bone forearm fractures. With proper patient selection, it provides faster healing and better function, making it a suitable option in modern orthopaedics practice